Suitability of cowpea sprouts to optimize rearing of biocontrol agents Phanerotoma syleptae (Zettel) and Liragathis javana (Bhat and Gupta) - Agountcheme, P.S.; Dannon, E.A.; Datinon, B.D.; Manbou, A.; Sinzogan, A.A.; Srinivasan, R.; Prittendrigh, B.R.; Tamò, Manuele (2024)
The legume pod borer Maruca vitrata Fabricius (Lepidoptera, Crambidae) is a key insect pest of cowpea, Vigna unguiculata Walp. The present study was designed to optimize the efficiency of mass rearing two of its biological control agents, the larval parasitoid Liragathis javana (Bhat and Gupta) and ovo-larval parasitoid Phanerotoma syleptae (Zettel), by comparing their performance on M. vitrata hosts reared on sprouting grains of 10 different varieties of cowpea as feeding substrate. Fecundity of M. vitrata and the two parasitoids were assessed per variety. Significant differences were observed between varieties for the development of unparasitzed larvae of M. vitrata and L. javana or P. syleptae-parasitized larvae. The cumulative daily fecundity shows different patterns: higher in IT 84D-449 for M. vitrata and L. javana but higher in Kpodji for P. sylepatae. Mortality of parasitized (by L. javana and P. syleptae) larvae and unparasitized (M. vitrata larvae) was lower in Kpodji variety. No significant differences were observed between male and female proportions (sex-ratio), regardless of insect species and cowpea variety except the varieties Tawa and Vitoco in L. javana. The mass rearing of M. vitrata and its two parasitoids’ species could be optimized using some cowpea varieties such as Kpodji and IT 84D-449 for biological control.